Recent Advances in Phenanthroindolizidine and Phenanthroquinolizidine Derivatives with Anticancer Activities - de Fatima Pereira, Maria; Rochais, Christophe; Dallemagne, Patrick (Anti-Cancer Agents in Medicinal Chemistry, 2015)
Phenanthroindolizidine and phenanthroquinolizidine derivatives constitute a series of compounds that are being intensively studied as potential anticancer agents. Related natural products such as antofine and tylophorine alkaloids are well known for their high cytotoxic activity; however, their clinical application has been limited because of their side effects. In this review we report, in detail, on the main structural modifications applied to the phenanthroindolizidine and phenanthroquinolizidine skeletons, and we also describe their associated anticancer activities. New derivatives with promising antitumoral activities have emerged. Simplified analogues were prepared using rapid synthetic routes, and a certain number of these analogues displayed increased anticancer activity and selectivity towards tumor cell lines. It is hoped that a better understanding of the mechanisms of action associated with structure–activity relationships (SAR) will enable us to rationalize the development of new anticancer drugs.
Keywords: antofine